Microscopic Examination of Nail Clippings from Patients with Palmoplantar Pustulosis - Anber Ancel Tanaka; Betina Werner; Cassia Farris; Cassio Tornesy (MDPI AG, 2019)
This study describes the clinical characteristics and microscopic findings of nails from 25 patients with palmoplantar pustulosis. Methods: This is a cross-sectional study of adult patients with clear-cut palmoplantar pustulosis. Onychodystrophy severity was evaluated in fingernails using the nail psoriasis severity index (NAPSI). A fragment of the most dystrophic fingernail was collected from each patient and submitted to routine histotechnical processing. The following microscopic parameters were evaluated: nail plate and subungual region thickness, presence or absence of parakeratosis, number of layers of parakeratosis, and presence of neutrophils, serous lakes, bacteria, blood, and fungi. Results: Twenty-one patients (84%) presented onychodystrophy with a mean NAPSI score of 12.67. The most common nail change was pitting (76.19% of patients). On average, nail plate thickness and subungual region thickness measured 0.42 and 0.14 mm, respectively. Neutrophils and fungi were not observed, but serous lakes were found in 4.7%, bacteria in 28.57%, blood in 4.76%, and parakeratosis in 19.05% of the patients. Conclusions: although palmoplantar pustulosis is a disease with great amounts of neutrophils in the epidermis, those cells were not found in the nail clippings studied herein. Furthermore, when clinical aspects and microscopic findings of palmoplantar pustulosis are compared to those of similar studies in psoriasis vulgaris, they show different characteristics.